Diversity and distribution of Laurencia sensu stricto (Rhodomelaceae, Rhodophyta) from the Mexican Pacific, including L. mutueae sp. nov. Issue 4 (10th May 2019) - Sentíes, Abel; Dreckmann, Kurt M.; Hernández, Oscar E.; Núñez Resendiz, María L.; Le Gall, Line; Cassano, Valéria
SUMMARY: The alpha diversity of Laurencia sensu stricto, as well as the majority of the other algal groups along the Mexican Pacific, was underestimated because very few studies had incorporated the use of molecular markers in taxonomic studies, which would allow a more realistic estimation of diversity, incluing new records and new species. The records of Laurencia s.s . for the Eastern Pacific (California, USA to Chile) currently represent 23% of its richness worldwide. In this work, we proposed an updated census of the currently recognized species of Laurencia s.s . for the Mexican Pacific. This checklist reported the occurrence of 22 species that represent 16% of the 137 species worldly recorded. We further included taxonomic remarks, type localities, and a detailed distribution for each species. In addition, we proposed a new species for this region, Laurencia mutueae sp. nov., based on morphological observation as well as phylogenetic analyses. The distribution in the Mexican Pacific revealed that the highest records of species were for the sub‐temperate region, while the localities along the Mexican tropical Pacific were poorly recorded. The scarcity of floristic affinities between the eastern and the western and central parts of the North Pacific Ocean was hypothesized to be a consequence of a strong isolation and hard barriers, such as the water masses between these regions.